2021
DOI: 10.1101/2021.02.05.429962
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhanced genetic analysis of type 1 diabetes by selecting variants on both effect size and significance, and by integration with autoimmune thyroid disease

Abstract: For polygenic traits, associations with genetic variants can be detected over many chromosome regions, owing to the availability of large sample sizes. The majority of variants, however, have small effects on disease risk and, therefore, unraveling the causal variants, target genes, and biology of these variants is challenging. Here, we define the Bigger or False Discovery Rate (BFDR) as the probability that either a variant is a false-positive or a randomly drawn, true-positive association that exceeds it in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…Insertion/deletion variants (indels), e.g., rs138300818, are not included in the eQTLgen data base comprising of 31,684 whole blood samples. Nevertheless, 22 out of 24 SNPs in the 96% posterior probability credible set for AAD association, all in high LD with rs138300818 (D’=1, r 2 >0.89 in 1000G GBR individuals), were significant eQTLs for THEMIS ( p -values < 1.9×10 −34 ) and ECHDC1 ( p -values < 1.30×10 −8 ) gene expression in whole blood, such that the minor alleles associated with protection from early onset type 1 diabetes were associated with lower THEMIS and ECHCD1 expression ( Supplementary Table S8 ). Our previous analysis indicated that the AAD association signal co-localises with the THEMIS eQTL signal (5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Insertion/deletion variants (indels), e.g., rs138300818, are not included in the eQTLgen data base comprising of 31,684 whole blood samples. Nevertheless, 22 out of 24 SNPs in the 96% posterior probability credible set for AAD association, all in high LD with rs138300818 (D’=1, r 2 >0.89 in 1000G GBR individuals), were significant eQTLs for THEMIS ( p -values < 1.9×10 −34 ) and ECHDC1 ( p -values < 1.30×10 −8 ) gene expression in whole blood, such that the minor alleles associated with protection from early onset type 1 diabetes were associated with lower THEMIS and ECHCD1 expression ( Supplementary Table S8 ). Our previous analysis indicated that the AAD association signal co-localises with the THEMIS eQTL signal (5).…”
Section: Resultsmentioning
confidence: 99%
“…While multiple TFs were predicted to bind to rs113297984 flanking sequence with DeepBind, the rs113297984 alleles did not affect their binding affinity. rs113297984 is in LD with rs138300818 (D’=1, r 2 =0.96 in 1000Genomes GBR population), and thus, has a similar eQTL profile. rs113297984 had a PCHiC interaction with PTPRK (CHiCAGO score 5.12) in thymus, in addition to interaction with THEMIS in GM12878 cell line (CHiCAGO score 11.54).…”
Section: Resultsmentioning
confidence: 99%
“…We firstly applied our multivariable approach using a large number of childhood and adult body size instruments to T1D data analysed previously in the study by Censin et al (n=5,913 cases and n=8,828 controls). Results from this analysis were then validated using a recent large-scale meta-analysis of up to 15,573 cases and 158,408 controls 21 . Analyses were then repeated separately in each contributing cohort from this meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, we investigated the opposite direction of effect using the same univariable methods mentioned above to assess whether genetic liability towards T1D risk influences body size in both childhood and adulthood in turn. In this analysis we used a set of genetic instruments for T1D identified from a recent meta-analysis (of up to 15,573 cases and 158,408 controls 21 ) and adult BMI was analysed as a continuous trait to derive a per standard deviation effect estimates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation